Ultra-wideband and off-optimised five-port reflectometer using power splitters - Lee, Kim Yee; Phua, Yeong Nan; Lim, Eng Hock; You, Kok Yeow; Cheng, Ee Meng; Abbas, Zulkifly (IEEE, 2018)
This paper presents an ultra-wideband (UWB) and off-optimised Five-Port Reflectometer (FPR) configured by power splitters. The proposed non-multi-state FPR is characterised and realised for complex reflection coefficient determinations. The measurement system can be easily setup using commercial power splitters, three detectors and a microwave source. The transmission lines method is used as calibration standard for FPR measurement system. Both the FPR setup and the transmission lines are characterised with a Vector Network Analyser prior to be used for the off-optimised measurement system. The results show good agreement between actual and calculated reflection coefficient for frequency range of 0.1 to 40 GHz. This novel FPR setup provides a simple, cost effective and accurate alternative in measuring broadband complex reflection coefficient.